2013
DOI: 10.4314/ejb.v15i1.1
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the hoverflies of northeastern Algeria (Diptera: Syrphidae)

Abstract: A survey of the hoverfly fauna of northeastern Algeria was carried out in 1991 and 1992, and seventy-three species recorded. Four species are new for Algeria: Dasysyrphus albostriatus, Chamaesyrphus lusitanicus, Brachypalpus laphriformis and Spilomyia maroccana. The genera Dasysyrphus, Chamaesyrphus and Brachypalpus are new for Algeria. Data on the distribution and the seasonal pattern of each species are provided. Species richness was found highest amongst wetlands (up to 38) and forested hills (up to 29). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Central and southern Europe, Morocco and Algeria(Dirickx 1994;Van Veen 2010). This species has not been reported in recent inventories in AlgeriaDjellab et al 2013;Haffaressas et al 2017) Larval trophic habits. Aphidophagous(Rojo et al 2003).15.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…Central and southern Europe, Morocco and Algeria(Dirickx 1994;Van Veen 2010). This species has not been reported in recent inventories in AlgeriaDjellab et al 2013;Haffaressas et al 2017) Larval trophic habits. Aphidophagous(Rojo et al 2003).15.…”
mentioning
confidence: 76%
“…The sampling conducted out in our study over a year indicates the presence of 37 species. During the period 1996-2010 and within the same climatic region of Algeria, Djellab et al (2013) reported the presence of 34 species, whereas a total of 73 species were listed under humid climate in the El-Kala region during 1991-1992, and 31species…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations